Economical and ecological impact of shelterbelts - Bošković, Jelena; Prijić, Željana; Ivanc, Aleksandar (Economics of Agriculture, 2010)
For the last several decades, ecologists have been warning the public about the issues of overuse and damage of natural resources, resulting in loss of biodiversity, and the need for environmental conservation. Vojvodina is a flat and deforested territory, characterised by strong winds causing wind erosion. Since planting forests on soils belonging to the first three categories was forbidden by the law, planting shelterbelts can provide a solution. They can provide relatively cheap and long-term solution. When properly planned, shelterbelts provide numerous economic, social and environmental benefits. They reduce wind impact, control snow spreading trapping it, protect livestock, buildings and gardens. Shelterbelts also provide habitat for wildlife and decorate the environment.